PARPs in lipid metabolism and related diseases. (November 2021) - Szántó, Magdolna; Gupte, Rebecca; Kraus, W. Lee; Pacher, Pal; Bai, Peter
Abstract: PARPs and tankyrases (TNKS) represent a family of 17 proteins. PARPs and tankyrases were originally identified as DNA repair factors, nevertheless, recent advances have shed light on their role in lipid metabolism. To date, PARP1, PARP2, PARP3, tankyrases, PARP9, PARP10, PARP14 were reported to have multi-pronged connections to lipid metabolism. The activity of PARP enzymes is fine-tuned by a set of cholesterol-based compounds as oxidized cholesterol derivatives, steroid hormones or bile acids. In turn, PARPs modulate several key processes of lipid homeostasis (lipotoxicity, fatty acid and steroid biosynthesis, lipoprotein homeostasis, fatty acid oxidation, etc.). PARPs are also cofactors of lipid-responsive nuclear receptors and transcription factors through which PARPs regulate lipid metabolism and lipid homeostasis. PARP activation often represents a disruptive signal to (lipid) metabolism, and PARP-dependent changes to lipid metabolism have pathophysiological role in the development of hyperlipidemia, obesity, alcoholic and non-alcoholic fatty liver disease, type II diabetes and its complications, atherosclerosis, cardiovascular aging and skin pathologies, just to name a few. In this synopsis we will review the evidence supporting the beneficial effects of pharmacological PARP inhibitors in these diseases/pathologies and propose repurposing PARP inhibitors already available for the treatment of various malignancies. Highlights: The activity of PARP enzymes is regulated by lipid molecules. PARP enzymes are involved in the regulation of lipid sensor transcription factors such as nuclear receptors or SREBPs. PARP activation is involved in the development of multiple diseases. These diseases include hyperlipidemia, dyslipidemia, AFLD, NAFLD, atherosclerosis, obesity and type II diabetes.